Brief Anti-Ageism Messaging Effects on Physical Activity Motivation Among Older Adults. (February 2022) - Menkin, Josephine A.; Smith, Jennifer L.; Bihary, Joseph G.
When people have more negative perceptions about aging or attribute health decline to old age, they engage in less health promotion behavior. We tested whether an intervention of brief anti-ageism messages addressing views of aging could motivate engagement in physical activities at senior centers. Attendees aged 50 and older ( n = 349; M age = 72, SD = 9) at seven centers were randomly assigned to read one of three intervention messages (different approaches addressing views of aging) or to not read a message before rating their likelihood of attending a variety of center programs, including physical activities. Multilevel regression models indicated the intervention increased motivation to attend physical activities compared with the control group among participants aged 72 and older. The three anti-ageism messages were similarly effective suggesting some flexibility in framing. The results indicate anti-ageism messages may be a scalable, low-cost approach to promoting physical activity in older adults.